High Fat Diet Decreases Neuronal Activation in the Brain Induced by Resistin and Leptin - Alsuhaymi, Naif; Habeeballah, Hamza; Stebbing, Martin J.; Badoer, Emilio (Frontiers in Physiology, 2017)
Resistin and leptin are adipokines which act in the brain to regulate metabolic and cardiovascular functions which in some instances are similar, suggesting activation of some common brain pathways. High-fat feeding can reduce the number of activated neurons observed following the central administration of leptin in animals, but the effects on resistin are unknown. The present work compared the distribution of neurons in the brain that are activated by centrally administered resistin, or leptin alone, and, in combination, in rats fed a high fat (HFD) compared to a normal chow diet (ND). Immunohistochemistry for the protein, Fos, was used as a marker of activated neurons. The key findings are (i) following resistin or leptin, either alone or combined, in rats fed the HFD, there were no significant increases in the number of activated neurons in the paraventricular and arcuate nuclei, and in the lateral hypothalamic area. This contrasted with observations in rats fed a normal chow diet; (ii) in the OVLT and MnPO of HFD rats there were significantly less activated neurons compared to ND following the combined administration of resistin and leptin; (iii) In the PAG, RVMM and NTS of HFD rats there were significantly less activated neurons compared to ND following resistin. The results suggest that the sensitivity to resistin in the brain was reduced in rats fed a HFD. This has similarities with leptin but there were instances where there was reduced sensitivity to resistin with no significant effects following leptin. This suggests diet influences neuronal effects of resistin.